Effect of Graphene Nanofillers on the Dynamic Mechanical Properties of Carbon Fiber–Epoxy Composites - V. Nikil Murthy; Dr. Ashwin C Gowda (Utilitas Mathematica, 2025)
The integration of nanomaterials into fiber-reinforced composites has opened new avenues for enhancing their mechanical and functional performance. The work aims to find out the storage modulus, and loss modulus concerning the Time, Frequency, and Temperature and compare the prepared sample values with each other to attain the optimum percentage of the graphene in the composite. The Novelty of the work is to give new ideas on the composite mixtures of epoxy filled with Graphene, carbon fiber-reinforced composite under dynamic loads. The results obtained by the testing of the samples by Dynamic mechanical analysis: Storage modulus and loss modulus. The maximum value of storage modulus of the 2% graphene sample is 15300 Mpa at 10Hz; 240 Celsius; 6 seconds, the loss modulus of the sample is 903 Mpa at 10Hz; 760 Celsius; 10 mins. For 4 % of the graphene sample, the storage modulus maximum value is 11700 Mpa at 10Hz; 260 Celsius; 6 seconds, the loss modulus of the sample is 862 Mpa at 5Hz; 710 Celsius; 8.7min. For a 6% sample, the storage modulus maximum value is at 4790 Mpa at 10Hz; 260 Celsius; 7.3min. The loss modulus of the sample maximum values is 457 Mpa at 0.1 Hz; 740 Celsius; and 9.7min. By comparing the values at different percentages of graphene, it is drawn that on increasing the percentage of the graphene (Nano filler) the value of the tensile, flexural, loss modulus decreases, and on increase in the percentage of the graphene in the composite the storage modulus also decreases for the parameters.